Toward the path of economic expansion in Nigeria: The role of trade globalization - Udi Joshua; Oladimeji M. Salami; Andrew A. Alola (African Governance and Development Institute (AGDI), 2020)
There are debates regarding the effect of globalization on national economies, and whether or not trade openness has a significant positive or negative influence on economic expansion and development. Thus, this study is aimed at investigating the relationship between trade globalization and Nigeria's economic advancement. The autoregressive distributed lags (ARDL) model was employed for the time series data: real GDP, openness, foreign direct investment and population growth over the period 1981-2017. The findings of this estimation revealed that population growth is significant but inhibitor of economic prosperity (real GDP) in the short-term. However, the significant and long-run determinants of the real GDP are population growth and trade openness but not foreign direct investment. Furthermore, the Granger Causality test revealed that real GDP granger causes population growth. The study therefore concluded that trade openness and globalization are necessary for Nigeria's economic expansion and development. Consequently, the study opined that the land border closure policy recently implemented by the Nigerian government might necessitate a significant reassessment so that the economic development projections of the country are not hindered.
Keywords: 330; Economic Expansion; Trade Globalization; Nigeria